Prevalance of trachoma in 13 Local Government Areas of Taraba State, Nigeria. (28th December 2018) - Umar, Murtala M.; Mpyet, Caleb; Muhammad, Nasiru; Adamu, Mohammed D.; Muazu, Habila; Onyebuchi, Uwazoeke; William, Adamani; Isiyaku, Sunday; Flueckiger, Rebecca M.; Chu, Brian K.; Willis, Rebecca; Pavluck, Alexandre L.; et al.
ABSTRACT: Background : The purpose of these surveys was to determine the prevalence of trachomatous inflammation—follicular (TF) in children aged 1–9 years and trichiasis prevalence in persons aged ≥15 years, in 13 Local Government Areas (LGAs) of Taraba State, Nigeria. Method : The surveys followed Global Trachoma Mapping Project (GTMP) protocols. Twenty-five households were selected from each of 25 clusters in each LGA, using two-stage cluster sampling providing probability of selection proportional to cluster size. Survey teams examined all the residents of selected households aged ≥1 year for the clinical signs TF, trachomatous inflammation—intense (TI) and trichiasis. Results : The prevalence of TF in children aged 1–9 years in the 13 LGAs ranged from 0.0–5.0%; Ussa LGA had the highest prevalence of 5% (95%CI: 3.4–7.2). Trichiasis prevalence ranged from 0.0–0.8%; seven LGAs had trichiasis prevalences above the threshold for elimination. The backlog of trichiasis in the 13 LGAs (estimated combined population 1, 959, 375) was 3, 185 people. There is need to perform surgery for at least 1, 835 people to attain a trichiasis prevalence in each LGA of <0.2% in persons aged ≥15 years. In six of the 13 LGAs, 80% of households could access washing water within 1 km of the household, but only one LGA had >80% of households with access to improved latrines. Conclusion : One of 13 LGAs requires antibiotic mass drug administration for active trachoma. Community-based trichiasis surgery needs to be provided in seven LGAs. There is a need to increase household-level access to improved washing water and latrines across the State.